Rapid screening test to estimate temperature optima for microalgae growth using photosynthesis activity measurements - Ranglová, Karolína; Lakatos, Gergely Ernö; Manoel, João Artur Câmara; Grivalský, Tomáš; Masojídek, Jiří (Folia microbiologica, 2019)
We have worked out a rapid 1-day test based on photosynthesis measurements to estimate suitable growth temperature of microalgae cultures. To verify the proposed procedure, several microalgae-Chlorella, Nostoc, Synechocystis, Scenedesmus, and Cylindrospermum-were cultured under controlled laboratory conditions (irradiance, temperature, mixing, CO2, and nutrient supply) to find the optima of photosynthetic activity using the range between 15 and 35 °C. These activities were recorded at each temperature step after 2 h of acclimation which should be sufficient as oxygen production and the PQ cycle are regulated by fast processes. Photosynthetic activity was measured using three techniques-oxygen production/respiration, saturating pulse analysis of fluorescence quenching, and fast fluorescence induction kinetics-to estimate the temperature optima which should correspond to high growth rate. We measured all variables that might have been directly related to growth-photosynthetic oxygen evolution, maximum photochemical yield of PSII, Fv/Fm, relative electron transport rate rETRmax, and the transients Vj and Vi determined by fast fluorescence induction curves. When the temperature optima for photosynthetic activity were verified in growth tests, we found good correlation. For most of tested microalgae strains, temperature around 30 °C was found to be the most suitable at this setting. We concluded that the developed test can be used as a rapid 1-day pre-screening to estimate a suitable growth temperature of microalgae strains before they are cultured in a pilot scale.
Keywords: kultivační techniky; Cyanobacteria; Light; Temperature; Chlorella; Photosynthesis; sinice; světlo; Culture Techniques; Kinetics; mikrořasy; Oxygen; teplota; Microalgae; kinetika; kyslík; fotosyntéza; Scenedesmus